Literatur Review: Performa Baterai Lithium-ion, Lithium-sulfur, dan Lithium-air sebagai Penggerak UAV Spionase Pertahanan dan Keamanan - ., Mohtar; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2024)
Currently, the development of science and technology is developing very quickly. One technology that is currently developing rapidly is unmanned aerial vehicles (UAV). This technology is believed to be a new breakthrough in the modern era because it minimizes human involvement in its operation. This increases effectiveness and reduces risk management in the operational field. Especially in the vast territory of the Unitary State of the Republic of Indonesia with diverse natural landscapes, UAV are considered very helpful as a means of defense and security equipment (alpahankam) in espionage. With these geographical conditions, to carry out its mission, a UAV requires a battery as the driving force. However, in general, the most widely used battery is the lithium-ion (Li-ion) type. It is known that there are several problems with Li-ion batteries, including not being able to withstand heat, being prone to exploding, and if the battery has a large capacity, the size of the battery must be large. Considering this situation, a study is needed to examine several alternative types of batteries, namely: lithium-air (Li-air) and lithium-sulfur (Li-S) batteries. This article aims to compare the performance of lithium-air batteries, and lithium-sulfur batteries which can later replace the use of lithium-ion batteries which are currently widely used in UAVs. The method used in writing this article is Systematic Literature Review (SLR) by searching, collecting and evaluating several sources related to the research object. From a comparison of the three batteries, Li-S batteries offer a large specific energy compared to Li-air and Li-ion batteries. Li-S batteries are currently receiving more attention so they are expected to move towards mass use more quickly. The results of this literature are that Li-S batteries have an energy density of 2,500Wh/kg and have exceeded the energy density of Li-ion batteries of 890Wh/kg and Li-air batteries of 250-1,200Wh/kg. Energy density determines how much energy can be accommodated in a cell of the same size. Thus, it is hoped that Li-S batteries will be a solution to problems with UAV batteries.